Constraints in the Primary Production of Bananas in the Davao Region, Philippines - Anzures, Arielle Francis; Hipolito, Kristina; Pestolante, Katherine; Navarrete, Al Faithrich (International Journal of Social and Management Studies, 2022)
This quantitative study examines the constraints in the primary production of bananas in Davao Region, Philippines. Various studies and climate projections by PAGASA proved the existence of climate change. Climatic variables (i.e. average temperature, rainfall amount, and relative humidity), Panama disease occurrence, and government support dataset are derived from government agencies from 1990-2019. Multiple regression analysis and other statistical tests are used. Most studies imply that there is a negative relationship between banana production to climate variables and panama disease but a positive relationship to government support. Results of this study show that climate variable indicators display a negative significant relationship on the volume of banana production which adheres to past studies while Panama disease and government support indicate an insignificant relationship which contradicts other studies. This study is therefore intended to impart practical knowledge to help farmers to be prepared for the adverse risks of climate change on their crops. It is also expected that this provides policy recommendations for the government to arrive at appropriate policies based upon ground realities.